A novel vertebrate system for the examination and direct comparison of the relative biological effectiveness for different radiation qualities and sources. (2nd November 2018) - Szabó, E. R.; Reisz, Z.; Polanek, R.; Tőkés, T.; Czifrus, Sz.; Pesznyák, Cs.; Biró, B.; Fenyvesi, A.; Király, B.; Molnár, J.; Brunner, Sz.; Daroczi, B.; et al.
Abstract: Purpose: The recent rapid increase of hadron therapy applications requires the development of high performance, reliable in vivo models for preclinical research on the biological effects of high linear energy transfer (LET) particle radiation. Aim: The aim of this paper was to test the relative biological effectiveness (RBE) of the zebrafish embryo system at two neutron facilities. Material and Methods: Series of viable zebrafish embryos at 24-hour post-fertilization (hpf) were exposed to single fraction, whole-body, photon and neutron (reactor fission neutrons () and ( p (18 MeV)+Be,  = 3.5 MeV) fast neutron) irradiation. The survival and morphologic abnormalities of each embryo were assessed at 24-hour intervals from the point of fertilization up to 192 hpf and then compared to conventional 6 MV photon beam irradiation results. Results: The higher energy of the fast neutron beams represents lower RBE (ref. source LINAC 6 MV photon). The lethality rate in the zebrafish embryo model was 10 times higher for 1 MeV fission neutrons and 2.5 times greater for p (18 MeV)+Be cyclotron generated fast neutron beam when compared to photon irradiation results. Dose-dependent organ perturbations (shortening of the body length, spine curvature, microcephaly, micro-ophthalmia, pericardial edema and inhibition of yolk sac resorption) and microscopic (marked cellular changes in eyes, brain, liver, muscle and the gastrointestinal system) changes scale together with the dose response. Conclusion: The zebrafish embryo system is a powerful and versatile model for assessing the effect of ionizing radiation with different LET values on viability, organ and tissue development.